What is the optimal dose of vitamin D in patients with osteoporosis?. Issue 11 (November 2017) - Wenstrup, Thomas; Hameed, Nabeel; Zhou, Alicia
Abstract : EVIDENCE‐BASED ANSWER : The answer is unclear. For daily dosing in patients older than 64 years, 792 to 2, 000 IU vitamin D per day decreases the risk of hip fracture by 30% and nonvertebral fracture by 14% compared with placebo (SOR: A, meta‐analysis RCTs). For monthly dosing in elderly patients with a prior fall, 24, 000 IU vitamin D leads to a lower incidence of falls at 1 year compared with higher monthly doses of vitamin D 60, 000 IU or vitamin D 24, 000 IU plus 300 μg calcifediol, but the effect compared with placebo is not known (SOR: B, single RCT).